Development of water-based printable piezoresistive sensors for large strain applications. (1st March 2017) - Gonçalves, B.F.; Oliveira, J.; Costa, P.; Correia, V.; Martins, P.; Botelho, G.; Lanceros-Mendez, S.
Abstract: Polymer based smart materials and, in particular, piezoresistive ones, are increasingly being used in a wide variety of applications ranging from automotive components to medical devices. This work reports on water-based piezoresistive polymer composites developed from thermoplastic poly (vinyl alcohol) (PVA) filled with carbon nanotubes (MWCNT) for the fabrication of high performance piezoresistive materials and sensors. PVA is a water-soluble synthetic polymer with suitable mechanical properties for the development of large strain sensors. MWCNT/PVA nanocomposites with good linearity between deformation and electrical resistance variation and with gauge factors up to 3 were achieved. Further, the materials were formulated in the form of inks for spray and screen printing of the sensors, which demonstrated a good performance for strain sensing both under laboratory tests conditions and when connected to a readout and communication system. Therefore, polymer based piezoresistive sensors were developed by a green approach and capable to be implemented by scalable printing technologies. Graphical abstract: Highlights: Water-based printable piezoresistive sensors were developed. The sensors are based on MWCNT/PVA composites. The stretchable sensors are suitable for large strain applications. The developed inks can be applied by screen and spray printing. The electronic readout system with RF communication was also developed.